Kesan bekerja dari rumah terhadap produktiviti pekerja: satu kajian dalam kalangan pekerja swasta di Selangor - Nur Amirah Mohd Khalidi; Lai Wei Sieng (Penerbit Universiti Kebangsaan Malaysia, 2025)
After the outbreak of the Covid-19 pandemic, working from home became the new norm in employment. Although life has largely returned to normal, many employees and employers continue to adopt working-from-home or hybrid models (a combination of working from home and the office). This is due to the numerous advantages of working from home. However, some employers and employees believe that the traditional mode of working from the office is more effective, particularly in terms of productivity and work performance. The purpose of this study is to identify how working from home affects employee productivity, aligning with the norms of today’s digital world. Data was collected through the distribution of questionnaire to 400 private-sector employees in Selangor. The data analysis was conducted using SPSS software and the results were based on descriptive statistical methods. The results of the study indicate that working from home significantly affects employee productivity. There are various important aspects in which working from home contributes to increased productivity and improved quality of work. In conclusion, working from home has a complex effect on employee productivity. To appropriate guidelines and rules. Interaction between employers and fellow employees is also essential to ensure effective communication and information sharing. Working from home helps enhance productivity and the quality of work in various ways. However, careful management of communication and collaboration is necessary to address challenges and maintain productivity.